Independent loss events of a functional tetherin gene in galliform birds - Krchlíková, Veronika; Lotke, Rishikesh; Haußmann, Isabell; Reinišová, Markéta; Kučerová, Dana; Pecnová, Ľubomíra; Ungrová, Lenka; Hejnar, Jiří; Sauter, Daniel; Elleder, Daniel (Journal of virology, 2023)
Birds represent important hosts for numerous viruses, including zoonotic viruses and pathogens with the potential to cause major economic losses to the poultry industry. Viral replication and transmission can be inhibited or blocked by the action of antiviral restriction factors (RFs) encoded by the host. One well-characterized RF is tetherin, a protein that directly blocks the release of newly formed viral particles from infected cells. Here, we describe the evolutionary loss of a functional tetherin gene in two galliform birds, turkey (Meleagris gallopavo) and Mikado pheasant (Syrmaticus mikado). Moreover, we demonstrate that the structurally related protein TMCC(aT) exerts antiviral activity in several birds, albeit by a mechanism different from that of tetherin. The evolutionary scenario described here represents the first documented loss-of-tetherin cases in vertebrates.
Keywords: Antigens, CD; Bone Marrow Stromal Antigen 2; Biological Evolution; CD antigeny; GPI-Linked Proteins; Animals; GPI-vázané proteiny; antigen stromálních buněk kostní dřeně; ptáci; Birds; zvířata; biologická evoluce